Colorectal Polyps in Young Patients Undergoing Colonoscopy - Bhusal, Yuvaraj; Basnet, Bhupendra Kumar; Shrestha, Ramila; Sharma Poudel, Mukesh; Khanal, Ajit; Silwal Poudyal, Nandu; Shah, Manoj Kumar; Khadka, Dibas; Bhusal, Surendra (Journal of Nepal Health Research Council, 2025)
Background: More than 10 % of colorectal carcinoma occur in patients less than 50 years. Progression of a colorectal polyp to carcinoma may take 5 to 20 years. Implementing screening guidelines and removing such polyps would reduce the progression into carcinoma. The aim of the study was to find the prevalence, distribution and histological analysis of polyps in patients under 50 years undergoing colonoscopy. Methods: Single-center cross-sectional study of 254 consecutive patients less than 50 years who underwent colonoscopy were included in the study. Patients with prior diagnosis of inflammatory bowel disease, colonic polyp(s) or colorectal carcinoma were excluded. Basic demographic data (age, gender), history of smoking and alcohol consumption were recorded. Prevalence of polyps, their location, size and histological type were estimated. Categorical data were expressed as frequencies and percentages. Results: Among 254 patients who underwent colonoscopy, 63 had colorectal polyps. 39 (61.9 %) patients with polyp were males and 33 (52.38 %) patients were of 40-49 years age. Recto-sigmoid polyps were seen in 47 (74.6 %) patients. Regular heavy alcohol consumers and active smokers had higher odds of having polyps. Adenomatous polyps and adenocarcinoma were detected in 12 and 10 patients respectively. Ulcerated or excavated appearance strongly suggested carcinomatous histology (OR: 363.8, (CI: 16.04 – 8250.90). Similarly, polyp size 5 mm or more favored adenomatous polyp or carcinoma [(OR: 177.35, CI: 9.7 – 3229)]. Conclusions: Prevalence of polyps in patients below 50 years age was 24.8 %. Most of the polyps were benign, diminutive (< 5 mm) and located in recto-sigmoid colon. One-third of the polyps were adenoma or adenocarcinoma. Keywords: Colonoscopy; colorectal polyp; screening